Jasmonate-Induced Defense Mechanisms in the Belowground Antagonistic Interaction Between Pythium arrhenomanes and Meloidogyne graminicola in Rice - Verbeek, Ruben E. M.; Van Buyten, Evelien; Alam, Md Zahangir; De Vleesschauwer, David; Van Bockhaven, Jonas; Asano, Takayuki; Kikuchi, Shoshi; Haeck, Ashley; Demeestere, Kristof; Gheysen, Godelieve; Höfte, Monica; Kyndt, Tina (Frontiers in Plant Science, 2019)
Next to their essential roles in plant growth and development, phytohormones play a central role in plant immunity against pathogens. In this study we examined the role of hormones in the antagonism of the plant-pathogenic oomycete Pythium arrhenomanes against the root-knot nematode Meloidogyne graminicola in rice roots. Hormone measurements and gene expression analyses showed that the jasmonate (JA) pathway is induced early upon P. arrhenomanes infection. Exogenous application of methyl-jasmonate (MeJA) on the plant confirmed that JA is needed for basal defence against both P. arrhenomanes and M. graminicola in rice. Whereas M. graminicola suppresses root JA levels to increase host susceptibility, Pythium inoculation boosts JA accumulation up to levels that can no longer be repressed by the nematode in double-inoculated plants. Exogenous MeJA supply phenocopied the defence-inducing capacity of P. arrhenomanes against the root-knot nematode, whereas the antagonism was weakened in JA-insensitive mutants. Transcriptome analysis confirmed upregulation of JA biosynthesis and signalling genes upon P. arrhenomanes infection, and additionally revealed induction of genes involved in biosynthesis of diterpenoid phytoalexins, consistent with strong activation of the gene encoding the JA-inducible transcriptional regulator DITERPENOID PHYTOALEXIN FACTOR. Next to that, our results provide evidence for induced expression of genes encoding ERF83, and related PR proteins, as well as auxin depletion in P. arrhenomanes infected rice roots, which potentially further contributes to the reduced nematode susceptibility seen in double-infected plants.